User fee removal for the poor: a qualitative study to explore policies for social health assistance in Iran - Manal Etemadi; Mohammad Hajizadeh (BMC, 2022)
Abstract Introduction Removal of user fee for vulnerable people reduces the financial barriers associated with healthcare payments, which, in turn, improves health outcomes and promotes health equity. This study sought to provide policy strategies to reduce user fee at the point of service delivery for the poor in Iran. Methods This is a qualitative study carried out in 2018. The purposive sampling method was applied, and 33 experts with relevant and valuable experiences and maximum variation to obtain representativeness and rich data were interviewed. Trustworthiness criteria were used to assure the quality of the results. The data were analyzed based on thematic analysis using the MAXQDA10 software. Results The most important issue regarding financial protection against user fee for the poor in Iran is policy integration and cohesion. Differences in access to financial support for user fee coverage among different groups of the poor have led to inequalities in access and financial protection among the poor. The suggested protection policies against the user fee at the point of service delivery in Iran can be categorized into three main categories: 1) basic health social insurance instruments, 2) free health services to the poor outside of the health insurance system, and 3) complementary insurance mechanisms. Conclusion Implementing a cohesive social assistance policy for all disadvantaged groups is needed to address inequalities in financial protection against user fee payment among the poor in Iran. Reducing user fee through mechanisms such as deductible cap, stop-loss, variable user fee and sliding fee scale can improve financial protection and enhance healthcare utilization among the poor. A user fee exemption is not enough to remove barriers to access to service for the poor, as other costs such as transportation expenditures and informal payments also put financial pressure on them. Therefore, financial support for the poor should be designed in a comprehensive protection package to reduce out-of-pocket payments for healthcare services, and indirect costs associated with healthcare utilization.